AS LEIS DO BABAÇU LIVRE E O DESENVOLVIMENTO ECONÔMICO: uma análise do conflito de interesses nas disputas socioambientais das regiões urbanas do Maranhão - Luane Lemos Felicio Agostinho (Universidade Federal do Maranhão, 2010)
The construction of the law always made by the disputes of interests of groups that form the society. The commencement of the Project of State Law nº 54/08, derogations to the ban on felling of palm trees for babassu in urban areas of metropolitan regions of the State of Maranhão highlights the conflict between the legalization of economic interests and preserve the environment and how of life of traditional communities of babassu coconut quebradeiras in urban regions of the state.